Negros Rainforest Conservation Project: Past, Present & Future - Turner, Craig; Slade, Eleanor; Ledesma, Gerardo (Silliman Journal, 2022)
The Negros Rainforest Conservation Project (NRCP) is a joint program of collaborative research, education, and training between the Negros Forests and Ecological Foundation, Inc. (NFEFI) and Coral Cay Conservation (CCC). The project is situated in the North Negros Forest Reserve (NNFR), Negros Occidental, the Philippines. The primary scientific objectives of the project are to collect biodiversity inventory data and to conduct complementary ecological research on species involved in the NFEFI species recovery program to aid in-situ conservation initiatives. The project utilizes trained volunteers to collect baseline biodiversity data in order to increase the understanding of the ecological dynamics and community composition of the different forest types within a restricted area of the NNFR. This paper presents an overview of the work of the NRCP and reports on the preliminary inventory and census data compiled by the project. These results do not only begin to confirm that the NNFR is an important biodiversity hotspot with a huge diversity of endemic and endangered species, but also underline the data gathering capacity of the NRCP. These initial empirical results and integrated approach of the NRCP are utilized to outline how this information could quantitatively underpin the conservation objectives of NFEFI, and contribute to the development of an integrated, community-driven conservation and sustainable management of the biodiversity of the NNFR.